2023
DOI: 10.1111/1468-5973.12517
|View full text |Cite
|
Sign up to set email alerts
|

Exercise design for interagency collaboration training: The case of maritime nuclear emergency management tabletop exercises

Rune Elvegård,
Natalia Andreassen

Abstract: In this paper, we explore a concept of exercise design within emergency management competence development. The paper presents recommendations for exercise design aspects that may be suitable for gaining collaboration skills and knowledge that responders need in unknown events of high complexity. This study explores the practice of tabletop exercises with complex scenarios that engage participants to discover organizational roles and responsibility division in collaborative action. Empirically, we base our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Exercise evaluation is an important component of exercise design, and with regard to the relational didactical model, it should relate to reaching learning outcomes within the setting framework and given exercise scenario and context. To achieve a credible exercise design, the evaluation approach must be planned thoroughly to mirror the participant prerequisites for learning and the learning process (Elvegård & Andreassen, 2023). Evaluation is an important step in organizational learning toward uncovering required improvements in capacity and capability, overall emergency management effectiveness and informed decision-making (Borodzicz & Van Haperen, 2002).…”
Section: Literature Review Emergency Preparedness Exercise Evaluation...mentioning
confidence: 99%
“…Exercise evaluation is an important component of exercise design, and with regard to the relational didactical model, it should relate to reaching learning outcomes within the setting framework and given exercise scenario and context. To achieve a credible exercise design, the evaluation approach must be planned thoroughly to mirror the participant prerequisites for learning and the learning process (Elvegård & Andreassen, 2023). Evaluation is an important step in organizational learning toward uncovering required improvements in capacity and capability, overall emergency management effectiveness and informed decision-making (Borodzicz & Van Haperen, 2002).…”
Section: Literature Review Emergency Preparedness Exercise Evaluation...mentioning
confidence: 99%
“…Guidelines provided by the United States Department of Homeland Security’s Exercise and Evaluation Program (HSEEP) and prior studies have shown that adapting the scenario to the context, characteristics, and settings similar to those that participants are likely to encounter in practice, is crucial for ensuring a meaningful experience for the participants ( 3–6 ). Exercises are built around hypothetical or “model” cities or communities, using a technique that is frequently used in emergency management and by the US Federal Emergency Management Agency for training purposes ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%